Using an Online Remote Laboratory for Electrical Experiments in Upper Secondary Education - Claesson, Lena; Håkansson, Lars (International Journal of Online and Biomedical Engineering (iJOE), 2012)
The use of remote laboratories in courses at university level has been reported in literature numerous times since the mid 90â??s. In this article focus is on activities carried out by teachers and students, at the Upper Secondary School Level, using the remote laboratory VISIR (Virtual Instrument Systems in Reality). The Upper Secondary School, Katedralskolan in Lund, Sweden, cooperate with Blekinge Institute of Technology, Sweden, in a project that concerns the introduction of remote laboratory environment suitable for Upper Secondary School science courses. A remote laboratory in electronics has been introduced and is used as a complement to the traditional workbench in the hands-on laboratory. Significant results from the project are; 1) the great interest shown by the students for the remote experiments, 2) the students appreciation for the fact that it was not simulations but actual real experiments, 3) the remote laboratory is easy to implement for use by both teachers and students and 4) it can be used simultaneously by many students.